Contributions to the morphology and histology of the genital system of Glossodoris capensis Barnard (nudibranchiata: glossodorididae) - Rossouw, G. J.(Gideon Johannes) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D. Sc.) -- University of Stellenbosch, 1976.